2016
DOI: 10.1557/jmr.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of DNA-immobilized magnetic particles and their utilization as an accumulative material of metal ions

Abstract: DNA-immobilized Fe 3 O 4 particles (DNA-Fe-particles) were prepared by mixing DNA, magnetic Fe 3 O 4 particles, and the silane coupling reagent, bis [3-(trimethoxysilyl)propyl]amine. The DNA-inorganic hybrid material was uniformly immobilized onto magnetic Fe 3 O 4 particles with the diameters of approximately 450 nm. These DNA-Fe-particles were stable in water. Additionally, we could simply collect the DNA-Fe-particles by a magnet from an aqueous solution. Therefore, we demonstrated the accumulation of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These phenomena suggested that the nucleic acid base in RNA interacts with the ―NH― group in the imino group of SiNSi through hydrogen bonding. On the other hand, when the SiNSi molecules were added to the RNA materials, the absorption band at 1203 cm −1 , which is related to the phosphate group, did not change. These results indicated that the SiNSi molecules did not interact with the phosphate group of RNA.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…These phenomena suggested that the nucleic acid base in RNA interacts with the ―NH― group in the imino group of SiNSi through hydrogen bonding. On the other hand, when the SiNSi molecules were added to the RNA materials, the absorption band at 1203 cm −1 , which is related to the phosphate group, did not change. These results indicated that the SiNSi molecules did not interact with the phosphate group of RNA.…”
Section: Resultsmentioning
confidence: 93%
“…Figure shows the IR spectra of (A) RNA without the hybridization, (B) RNA‐10 wt% SiNSi hybrid, (C) RNA‐20 wt% SiNSi hybrid, (D) RNA‐30 wt% SiNSi hybrid, (E) RNA‐50 wt% SiNSi hybrid, (F), RNA‐70 wt% SiNSi hybrid, and (G) dried SiNSi materials. The RNA material indicated absorption bands at 1676, 1635, and 1203 cm −1 , related to the stretching vibration of C═O in the nucleic acid base, the stretching vibration of C═N in the nucleic acid base, and the antisymmetric stretching vibration of the phosphate group, respectively . The intensity ratio of the absorption bands at 1676 cm −1 and 1635 cm −1 changed by the addition of the SiNSi molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations